Success in solving mathematical word problems in gifted and non-gifted students - Budínová, Irena (Scientia in educatione, 2025)
One approach to identifying mathematical talent in students is to work with complex word problems, the solution of which can be influenced by the nature of the problems and different talent profiles. The study focuses on how these factors influence the identification of mathematically gifted students in the 5th grade of primary school. The aim was (1) to determine the degree of correlation between three methods of identifying talent–teacher assessment, standardized test results and research didactic test results – and (2) to identify tasks that best distinguish gifted students from others. The research test included five subtests, four algebraic and one combinatorial, focused on manifestations typical of gifted students, such as flexibility of thinking, ability to generalize and creativity in problem solving. The study emphasizes the analysis of the subtest with tasks of the “I think of a number” type, which allow to reveal hidden manifestations of talent and contribute to its more accurate diagnosis. The research involved 45 students from a school focused on supporting the gifted. The pilot nature of the study is intended to serve as a basis for the creation of a standardized test for students in grades 5–7. The results show a moderate to strong correlation between the methods used, but also the existence of phenomena that may lead to the overlooking of mathematically gifted students.